Pengaruh Teknik Relaksasi Hypnobirthing Terhadap Penurunan Rasa Nyeri Kala I Persalinan Normal Pada Primipara di BPM Evi - Liza Safitri, Yulrina Ardhiyanti, (Jurnal Martenity and Neonatal, 2016)
Hypnobirthing is one of technique otohipnosis (self hypnosis) the efforts natural infuse intention positive / suggestion to people / the unconscious mind to operate in pregnancy and preparation childbirth. Primipara was a woman who gave birth to for the first time and tend to more often undergo pain who was stronger than a multiparous. Midwife practice in Pekanbaru that uses hypnobirthing is BPM Evi. The study is done to know the influence of hypnobirthing relaxation techniques to decrease pain in first stage normal childbirth in primipara at BPM Evi 2015. The research is a quasi research experiment with the design pretes–postest with control group. The total sample as many as 36 people are 18 people respondents as experimentation and 18 people respondents as control. The sample procedure used accidental sampling technique.The data taken by using kuisioner and analysis of data was undertaken in univariat and bivariat by T–independent test. The results of the study obtained that there are the influence of hypnobirthing relaxation techniques to decrease pain in first stage normal childbirth in primipara after hypnobirthing doing. Should pregnant women and that women about maternity attended a class pregnant women who do not to focus about pregnancy it was about hypnobirthing and suggested to use hypnobirthing relaxation techniques to ease the pain in first stage childbirth.